Prevalence and diversity of Eimeria spp. in free-range chickens in northeastern Brazil - Silva, Juliana Trajano da; Alvares, Felipe Boniedj Ventura; Lima, Estefany Ferreira de; Silva Filho, Geraldo Moreira da; Silva, Ana Luzia Peixoto da; Lima, Brendo Andrade; Feitosa, Thais Ferreira; Vilela, Vinícius Longo Ribeiro (Frontiers in Veterinary Science, 2022)
In tropical regions, family farming is a form of production and work that is highly present in rural areas. Because the production system for free-range chickens has a low level of technification, it frequently presents massive infection by coccidia. The objective of this study was to determine the prevalence and diversity of Eimeria species in free-range chickens in northeastern Brazil. Fecal analyses were carried out using materials collected from 100 farms, belonging to 10 different municipalities. The sample from each farm was composed of five stool samples collected from different animals. Coproparasitological analyses were performed and, in each positive sample, photomicrographs of 20 oocysts were used for morphological identification of coccidia. The presence of Eimeria spp. was detected in 59% (59/100) of the farms analyzed. Species identification was performed through morphometric analysis of 1,180 sporulated oocysts. The following eight species of Eimeria spp. were found, in decreasing order of prevalence: Eimeria necatrix (25%), Eimeria mitis (18.3%), Eimeria mivati (17.3%), Eimeria tenella (12.4%), Eimeria brunetti (9.9%), Eimeria acervulina (9.1%), Eimeria praecox (4.8%) and Eimeria maxima (3.2%). The prevalence and diversity of Eimeria spp. on farms producing backyard chickens in the semiarid region of Brazil were high, especially the diversity of species. Changing the management, with the adoption of sanitary measures, may be effective in reducing the high prevalence of coccidia on the farms studied.